Promoting H2 Activation over Molybdenum Carbide by Modulation of Metal‐Support Interaction for Efficient Catalytic Hydrogenation. Issue 14 (26th June 2021) - Ma, Ling; Chen, Ping; Zhang, Guangji; Wang, Liqiang; Tang, Feiying; Zhao, Xiaojun; Wang, Jin; Huang, Jianhan; Liu, You‐Nian
Abstract: Transition metal carbides (TMCs) have been used extensively as catalysts for hydrogenation reactions. However, TMC catalysts suffer from low activity for H2 activation, which is vital to their hydrogenation performance. Herein, we report a feasible strategy to improve the ability of TMCs (e. g., Mo2 C) for H2 activation by modulation of the metal‐support interaction (MSI). The MSI can be tuned by introducing N element into carbon supports. Specifically, N can modulate the orbital structure of Mo to promote H2 activation. Experimental and theoretical results reveal that H2 activation ability of the metal sites can be altered by loading them onto carbon supports, and optimized by doping N into the corresponding carbon matrices. Consequently, N‐doped carbon‐supported Mo2 C (Mo2 C/NC) catalyst, possessing improved H2 activation ability, displays remarkably enhanced catalytic hydrogenation performance for the reduction of nitro compounds. The conversion and selectivity over Mo2 C/NC are nearly 100 % under mild conditions. Abstract : Thanks for your support : Hydrogenation performance of transition metal carbides can be improved by enhancing their H2 activation ability, which can be achieved by introducing and modulating the metal‐support interaction (MSI). Compared with Mo2 C and Mo2 C/C, Mo2 C/NC performs better in hydrogenating nitro compounds into amino compounds.